Investigating the efficacy and improved stability against Staphylococcus aureus of Lynronne-1D, a modified rumen microbiome derived antimicrobial peptide. Issue Volume 1(2019)Issue A (8th March 2019) - Lawther, Katie; Oyama, Linda; Huws, Sharon
Abstract : Antimicrobial resistant infections are at a crisis point, posing a massive threat to human health with an anticipated annual mortality of 10 million people by 2050. Antimicrobial peptides (AMPs) are a promising solution to treat drug resistant infections, with the highly competitive ecosystem of the rumen microbiome being a fruitful resource for mining AMPs. In this study, we aimed to improve the stability of a known rumen AMP with great therapeutic potential, Lynronne-1. This AMP is efficacious against topical skin infections of Methicillin resistant Staphylococcus aureus but has no activity in systemic infections when administered intravenously due to degradation by peptidases. To overcome this hurdle and improve its use intravenously, we substituted the L isoforms N and C terminal amino acid residues to d-isoforms, thereby increasing the stability of the peptide in the presence of trypsin by three-fold. The activity of the modified peptide, named Lynronne-1D against S. aureus was subsequently investigated. Lynronne-1D retained its antimicrobial activity with an MIC of 8 µg ml −1 against S. aureus and improved MICs (>4 fold) in Gram-negative bacteria strains. The peptide had rapid and potent bactericidal activity causing a ≥6 log c.f.u./ml reduction in viable S. aureus cells within 30 min of treatment. It induced membrane permeabilization within 5 min and successfully prevented biofilm formation by S. aureus cells. Lynronne-1D was also non-cytotoxic to mammalian blood cells. The improved properties of Lynronne-1D over the original peptide makes it a promising therapeutic agent for the treatment of systemic infections of S. aureus .